A qualitative study of patients' knowledge and views of about oral health and acceptability of related intervention in an Australian inpatient alcohol and drug treatment facility. (20th January 2017) - Cheah, Alison Li Sun; Pandey, Ram; Daglish, Mark; Ford, Pauline J.; Patterson, Sue
Abstract: Social factors, health behaviours and the direct effects of substances contribute to the poor oral health and restricted access to dental services experienced by people who are dependent on drugs and/or alcohol. Admission for inpatient withdrawal management provides an opportunity for intervention to promote oral health but to be effective it must be acceptable to patients. To support intervention design, we examined patients' views about oral health, practices and treatment access, and appropriateness of health‐promoting intervention in this context. Given paucity of knowledge in the area we employed a qualitative approach, data were collected in semi‐structured interviews with inpatients of a public specialist alcohol and drug unit in Australia in September 2014. Analysis employed the framework approach. All 14 participants wanted 'good teeth' but few diligently attended to oral healthcare; most sought assistance only in emergencies. Participants' knowledge of services was limited and practical and affective barriers hindered access. With none recalling attention to oral health during admission, support was strong for incorporation of oral health in inpatient assessments. Participants wanted information about the impact of substances on oral health and oral hygiene practices provided in various formats, and facilitated referral to non‐judgemental, affordable treatment. Patients regarded promotion of oral health in the inpatient context as important, relevant and acceptable. Support should respect the different knowledge, practices and motivations for oral health and recovery, of patients. Addressing practical and affective barriers to dental services will require collaboration between drug and alcohol and dental services, and this should be the focus of further research.